Algebra

posted by .

checking problem
Use FOIL to multiply:
(6x – 1)(3x – 4)
6x*3x + 6x*(-4) + (-1)*3x + (-1)*(-4) =
6x*3x = 18x^2
6x*-4 = -24x
-1*3x = -3x
-1* -4 = 4

18x^2 – 24x -3x +4 =
18x^2 – 27x + 4

  • Algebra -

    Thats right! :)

  • Algebra -

    Thankyou.

    Any insight on this next one?

    (x^4y^6z^12/9^-2x^3y^-8z^-9)^0

    I am not sure why but i get the answer
    1/9^0

    I was thinking the ^0 multiplies everything to 0 but the 9.

  • Algebra -

    John,
    (anything) = 1 except 0^0 which is undefined

  • Algebra -

    Anything to the 0 power is 1. And somehow my final answer was

    xz^3 / 9^-2y^-2

    but i really could be wrong, hopefully someone else can help u with this one cause im not positive!

  • Algebra -

    6xy/9y4x30x3y/-48x

  • Algebra -

    -5(x+1)+3x+2=6x+4

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

  1. BobPursley..here it is:

    Problem 1: (x-2)/(3x+4) - 6x/(x+1) What I did: Common denominator is: (3x+4)(x+1) (x-2)(x+1)/(3x+4)(x+1) - 6x(3x+4)/(x+1)(3x+4) [(x-2)(x+1) - 6x(3x+4)] / (x+1)(3x+4) (x^2 - x - 2 - 18x^2 - 24x) / (x+1)(3x+4) x^2 - 18x^2 = -17x^2 -x …
  2. Algebra (Re.: Reiny)

    The fact that there was that nice symmetry to the question, makes it easier than it first appears. I had it as: (a/b + b/a)÷(b/a - a/b) look at (a/b + b/a) the common denominator for this would be ab, so a/b + b/a = (a^2 + b^2)/ab …
  3. Math

    Find the HCF of f(x) = 6x^3 + 24x^2 + 18x, g(x) = 4x^4 + 4x^3 - 24x^2
  4. Algebra 2

    Find the LCD of 5/18x^2y^3,-3/24x^4y^5
  5. algebra

    -12x^6+24x^5-18x^2/-6x^2 3x^4+x^3-3x check see if I did it right.
  6. algebra

    -12X^6+24x^5-18x^2/-6x^2=2x^4+24x^3-3x could some one check this for me please
  7. algebra

    Did I do this problem the correct way if so is there a shorter way to explain this?
  8. algebra

    Reduce answers to lowest terms. 1.) 2x/2x^2+5x-3 + 5/x^2-9 = 2.) x-3/12x^3-18x^2 - x+1/16x^2-24x = 3.) 2x/x^2-2x-15 - x-2/3x^2+9x =
  9. Math

    Find the Least Common multiple of the two expressions: 24x^2-96 & 18x^2+18x-36
  10. Math

    (2x-1)(3x-7)(4x+3) =6x^2-14x-33x+7 =(6x^2-19x+7)(4x+3) =24x^3+18x^2-126x+28x+21 =24x^3+18x^2-88x+21 <-- my answer but the correct answer is 24x^3-50x^2-23x+21 please correct me?

More Similar Questions